Karakteristik dan Kelimpahan Mikroplastik pada Sedimen dan Air di Teluk Jimbaran, Bali - Agnes, Intancia; Hendrawan, I Gede; Astawa Karang, I Wayan Gede (Journal of Marine Research and Technology, 2024)
Microplastics are plastic particles that are less than 5 mm in size. Many plastic wastes on the sea surface and marine sediments disrupt coastal and marine ecosystems. This study aimed to identify the characteristics of color, size, and type and the abundance of microplastics in water and sediments in Jimbaran Bay, Bali Island. Water sampling using manta trawls and glass bottles and sediment sampling using shovels and jars. Laboratory analysis methods by filtering, drying, Wet Peroxide Oxidation, density separation, and observing the presence of microplastics using a stereo microscope, then documented with the Optilab and measured with image raster. The results of observing the presence of microplastics based on the type in water are fragments, filaments, fibers, foam, pellets, and microplastics, and in sediments are fibers, fragments, and filaments with a total of 16 colors. The average abundance of microplastics in water samples was 4.398 particles/m 3 and in sediments 15.115 particles/kilogram of dry sediment. This research shows that Jimbaran Bay is contaminated with microplastics. Furthermore, this research can become a reference for other research and can be the basis for efforts to reduce plastic waste in the oceans.